Development of defect-free and hyperthin-skinned of asymmetric cellulose acetate membrane from binary dope system for gas separation - Abd. Rahman, Sunarti (2004)
The objective of this study is to develop of a defect-free and hyperthinskinned asymmetric cellulose acetate (CA) membrane for gas separation with binary system of dope solution (one polymer and one solvent). The membranes were developed from a binary system which consisted of 23 wt.% cellulose acetate and 77 wt.% N- methyl pyrrolidone using a dry/wet phase inversion process. Flat sheet membranes were cast using a pneumatically-controlled casting machine. Ethanol and N-hexane were used as solvents for solvent exchange process. Pure hydrogen and nitrogen were used as test gases in the permeation experiment using feed pressure range of 1 to 5 bar. Various casting speed were applied in the process which represented different shear rates, ranging between 85.33 s-1 to 304.76 s-1 in order to investigate the effect of fabrication conditions on the performance of the newly developed membranes. The evaporation time was also considered an important parameter for the formation of asymmetric membrane. Thus, the membranes fabricated at different evaporation time ranges between 3 s to 25 s were analyzed in this study. The produced membranes were then characterized by scanning electron microscopy (SEM). This study found that at high shear, the membrane comprised a hyperthin skin layer with finger-like porous substructure and skin thickness in the range 4 Ã…-300 Ã… from calculation. The rheologically induced molecular orientation was believed to contribute to these results and the orientation was measured directly using plane polarized reflectance infrared spectroscopy technique. High shear membranes exhibited greater molecular orientation in skin layer. This can be clearly represented by the higher peaks at specific functional groups in the normalized different spectrum. At optimum shear rate (213.33 s-1) and optimum evaporation time (15 s), pressure-normalized flux and selectivity of this membrane were relatively higher compared to conventional membranes and surpassed that of the intrinsic selectivity of cellulose acetate polymer film. As conclusion, the combined effects of phase inversion and rheological factors were successfully employed to developed defect-free and hyperthin-skinned asymmetric cellulose acetate membrane using binary system of dope solution.